2017
DOI: 10.18488/journal.107.2017.54.191.198
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Socio-Economic Impact of China Pakistan Economic Corridor

Abstract: Article HistoryRoad and transport corridor play a significant role in the development of the country. This study examines the socio economic impact of China Pakistan Economic Corridor. Pakistan and China has great relations from the beginning. China Pakistan economic corridor is very significant for both countries as it provide access of China to the warm water of Arabian Sea through a short and safe route which will save billions of shipping charges and time and will cover the current energy crises in Pakista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 2 publications
1
28
1
Order By: Relevance
“…Table 3 shows that 13.2% of the respondents thought that the CPEC had a role in the improvement of Pakistan's economy, 11.8% of them said that the CPEC had a role in fulfilling the energy needs of Pakistan, 22.0% of them thought that the CPEC had role in rural and urban development, 19.6% of them said that the CPEC had a role in social development of Pakistan, and 19.6% of the respondents thought that the CPEC had a role in all aforementioned indicators of progress. Reference [47] concluded that the CPEC is based upon the establishment of a railroad, a road (2700 km), and an oil and gas pipeline between China and Pakistan. The linkage between Pakistan and China will provide a cost-saving shipment and secure route to China for business and trade with the rest of the world.…”
Section: X 4 (Predictor Variables)mentioning
confidence: 99%
“…Table 3 shows that 13.2% of the respondents thought that the CPEC had a role in the improvement of Pakistan's economy, 11.8% of them said that the CPEC had a role in fulfilling the energy needs of Pakistan, 22.0% of them thought that the CPEC had role in rural and urban development, 19.6% of them said that the CPEC had a role in social development of Pakistan, and 19.6% of the respondents thought that the CPEC had a role in all aforementioned indicators of progress. Reference [47] concluded that the CPEC is based upon the establishment of a railroad, a road (2700 km), and an oil and gas pipeline between China and Pakistan. The linkage between Pakistan and China will provide a cost-saving shipment and secure route to China for business and trade with the rest of the world.…”
Section: X 4 (Predictor Variables)mentioning
confidence: 99%
“…Extensive literature on social, economic, cultural and environmental impacts of road and transportation on local people is present. Earlier studies have studied the impact of road and transportation, including social (Cramphorn and Davies, 2004;Geurs et al, 2008;Windle and Cramb, 1999;Ali et al, 2017b;Grootaert and Calvo, 2002) economic (Ali et al, 2016;Asomani-Boateng et al, 2015;Moore, 2012;Ali et al, 2017b) and environmental impacts (Fischer, 1999;Carrier et al, 2016;Strogen et al, 2016;WHO, 2000). In other words, the impacts of road and transportation on local residents have been studied; however, their support for road and transport infrastructure has never been examined earlier.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Transport infrastructure provides many opportunities for the host community, as recent studies by Asomani-Boateng et al (2015) and Ali et al (2017a) revealed that road and transportation has a noteworthy social and economic impact on residents of the area. Road and transportation improves the living standard of the native dwellers and is considered as a plan for the development and improvement of the region (Ramachandran and Linde, 2011;Ali et al, 2017aAli et al, , 2017b. Road and transportation is a project that is very beneficial for the locals and is always supported by the local people.…”
Section: Introductionmentioning
confidence: 99%
“…The China-Pakistan Economic Corridor (CPEC) is a pioneer project of the Belt and Road Initiative, where China has planned to interlink global communities through road and railway networks [27,28]. The project passes through 300 km from Gilgit-Baltistan (GB), northern Pakistan.…”
Section: Growth and Sustainability Of Mses In The Context Of The Cpecmentioning
confidence: 99%